2013
DOI: 10.1128/aac.01052-13
|View full text |Cite
|
Sign up to set email alerts
|

KPC-Producing, Multidrug-Resistant Klebsiella pneumoniae Sequence Type 258 as a Typical Opportunistic Pathogen

Abstract: The virulence of a KPC-producing Klebsiella pneumoniae sequence type 258 (ST258) strain representing those circulating in Greece was assessed in a mouse septicemia model. The strain was virtually avirulent (50% lethal dose, >10 8 and 5 ؋ 10 7 CFU for immunocompetent and neutropenic animals, respectively). Also, it was highly susceptible to serum killing, rapidly phagocytosed in vitro, and classified as K41, which is not among the virulent capsular types. The findings indirectly support the notion that high ST2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 15 publications
(12 reference statements)
9
79
4
1
Order By: Relevance
“…Likewise, the virulence of KPC-carrying ST258 strains is being tested in a variety of assays and infection models to determine whether wide dissemination correlates with increased virulence. Notably, strains of ST258 are less virulent in mice than another K. pneumoniae strain, ATCC 43816 (ST439), which is frequently used in mouse studies (21,22). Furthermore, in mouse infections, an ST258 strain was markedly more sensitive to clearance by monocytes than by neutrophils (22), and in cell culture, an ST258 strain was phagocytosed by murine macrophages more efficiently than an ST439 strain (ATCC 43813) (21).…”
Section: Classical Antibiotic-resistant Emerging and Hypervirulentmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the virulence of KPC-carrying ST258 strains is being tested in a variety of assays and infection models to determine whether wide dissemination correlates with increased virulence. Notably, strains of ST258 are less virulent in mice than another K. pneumoniae strain, ATCC 43816 (ST439), which is frequently used in mouse studies (21,22). Furthermore, in mouse infections, an ST258 strain was markedly more sensitive to clearance by monocytes than by neutrophils (22), and in cell culture, an ST258 strain was phagocytosed by murine macrophages more efficiently than an ST439 strain (ATCC 43813) (21).…”
Section: Classical Antibiotic-resistant Emerging and Hypervirulentmentioning
confidence: 99%
“…Notably, strains of ST258 are less virulent in mice than another K. pneumoniae strain, ATCC 43816 (ST439), which is frequently used in mouse studies (21,22). Furthermore, in mouse infections, an ST258 strain was markedly more sensitive to clearance by monocytes than by neutrophils (22), and in cell culture, an ST258 strain was phagocytosed by murine macrophages more efficiently than an ST439 strain (ATCC 43813) (21). The inability of mouse neutrophils to effectively target strains of ST258 is consistent with data from recent studies with human neutrophils, where an ST258 strain was more resistant to killing by human neutrophils than a closely related ST11 strain or a Staphylococcus aureus control (23,24).…”
Section: Classical Antibiotic-resistant Emerging and Hypervirulentmentioning
confidence: 99%
“…ST258 lacks well-characterized K. pneumoniae virulence factors, including the K1, K2, and K5 capsular antigen genes; the aerobactin genes; and the regulator of mucoid phenotype gene, rmpA (156). A recent study demonstrated that ST258 is nonvirulent in animal models, is highly susceptible to serum killing, and can rapidly undergo phagocytosis (156).…”
Section: Recent Developments Pertaining To K Pneumoniae St258mentioning
confidence: 99%
“…However, it should be noted that enhanced virulence might be unnecessary for KPC-producing K. pneumoniae to cause disease. Indeed, despite showing a low virulence in animal models, the widespread ST258 clone is a well-known cause of infection in hospitalized patients, even in subjects without a severe degree of immunodeficiency (15)(16)(17).…”
Section: Case Reportmentioning
confidence: 99%